Combating Actions of Green 2D-Materials on Gram Positive and Negative Bacteria and Enveloped Viruses - Singh, Manjot; Zannella, Carla; Folliero, Veronica; Di Girolamo, Rocco; Bajardi, Francesco; Chianese, Annalisa; Altucci, Lucia; Damasco, Achille; Del Sorbo, Maria Rosaria; Imperatore, Concetta; Rossi, Manuela; Valadan, Mohammadhassan; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Interactions of novel bi-dimensional nanomaterials and live matter such as bacteria and viruses represent an extremely hot topic due to the unique properties of the innovative nanomaterials, capable in some cases to exhibit bactericide and antiviral actions. The interactions between bacteria and viruses and two dimensional nanosheets are here investigated. We extensively studied the interaction between a gram-negative bacterium, Escherichia coli, and a gram-positive bacterium, Staphylococcus aureus, with two different types of 2D nanoflakes such as MoS2, belonging to the Transition Metal Dichalcogenides family, and Graphene Oxide. The same two types of nanomaterials were employed to study their antiviral action towards the Herpes simplex virus type-1, (HSV-1). The experimental results showed different bactericide impacts as well as different antiviral power between the two nanomaterials. The experimental findings were interpreted in bacteria on the base of the Derjaguin-Landau-Verwey-Overbeek theory. A simple kinetic model of bacterial growth in the presence of the interacting nanosheets is also elaborated, to explain the observed results. The experimental results in viruses are really novel and somewhat surprising, evidencing a stronger antiviral action of Graphene Oxide as compared to MoS2. Results in viruses are complicated to quantitatively interpret due to the complexity of the system under study, constituted by virus/host cell and nanoflake, and due to the lack of a well assessed theoretical context to refer to. Thus, these results are interpreted in terms of qualitative arguments based on the chemical properties of the interactors in the given solvent medium.